224k views
3 votes
Simplify -7 2/3+(-5 1/2)+8 3/4

User Altandogan
by
6.1k points

1 Answer

5 votes

Given the expression:


-7(2)/(3)+(-5(1)/(2))+8(3)/(4)

First, we open the bracket:


=-7(2)/(3)-5(1)/(2)+8(3)/(4)

Next, change each of the fraction to an improper fraction


=-(23)/(3)-(11)/(2)+(35)/(4)

We look for the lowest common multiple of the denominators.

LCM of 3, 2 and 4=12

Therefore:


\begin{gathered} -(23)/(3)-(11)/(2)+(35)/(4)=(-23(4)-11(6)+35(3))/(12) \\ =(-92-66+105)/(12) \\ =-(53)/(12) \\ =-4(5)/(12) \end{gathered}

User Taj
by
5.2k points